Breath-by-breath assessment of acute pulmonary edema using electrical impedance tomography, spirometry and volumetric capnography in a sheep (Ovis Aries) model - Raisis, Anthea; Mosing, Martina; Sacks, Muriel; Hosgood, Giselle; Schramel, Johannes; Blumer, Sarah; Böhm, Stephan H. (Frontiers in Veterinary Science, 2024)
The bedside diagnosis of acute pulmonary edema is challenging. This study evaluated the breath-by-breath information from electrical impedance tomography (EIT), respiratory mechanics and volumetric capnography (VCap) to assess acute pulmonary edema induced by xylazine administration in anesthetized sheep. Objective: To determine the ability and efficiency of each monitoring modality in detecting changes in lung function associated with onset of pulmonary edema. Methods: Twenty healthy ewes were anesthetized, positioned in sternal (prone) recumbency and instrumented. Synchronized recordings of EIT, spirometry and VCap were performed for 60 seconds prior to start of injection, during xylazine injection over 60 seconds (0-60 seconds) and continuously for one minute (60-120 seconds) after the end of injection. Statistical analysis was performed using a mixed effect model for repeated measures with Bonferroni's correction for multiple comparisons, to determine at which breath after start of injection the variable was significantly different from baseline. A significant change over time was defined as an adjusted p< 0.05. Statistics were performed using GraphPad Prism 0.1.0. Results: Electrical impedance tomography showed significant changes from baseline in all but two variables. These changes were observed simultaneously during xylazine injection at 48 seconds and were consistent with development of edema in dependent lung (decreased endexpiratory lung impedance, ventilation in centro-ventral and ventral lung region) and shift of ventilation into non-dependent lung (decreased non-dependent silent spaces and increased center of ventilation ventral to dorsal and increased ventilation in centro-dorsal and dorsal lung region). All changes in lung mechanics also occurred during injection, including decreased dynamic respiratory system compliance and increased peak expiratory flow, peak inspiratory pressure and airway resistance at 48, 54 and 60 seconds respectively. Changes in VCap variables were delayed with all occurring after completion of the injection.In this model of pulmonary edema, EIT detected significant and rapid change in all assessed variables of lung function with changes in regional ventilation indicative of pulmonary edema. Volumetric capnography complemented the EIT findings, while respiratory mechanics were not specific to lung edema. Thus, EIT offers the most comprehensive method for pulmonary edema evaluation, including the assessment of ventilation distribution, thereby enhancing diagnostic capabilities..